World Englishes in the Middle East and North Africa (MENA). Issue 2 (22nd May 2020) - Elyas, Tariq; Mahboob, Ahmar
Abstract: This special issue highlights the importance of world Englishes research in the Arabic‐speaking and non‐Arabic Middle East and North Africa (MENA) region. Scrutiny of the world Englishes (WE) research literature suggests that the MENA region is largely understudied and undertheorized, and that there is a lacuna in research with reference to this topic. The use of English in this geopolitical region is diverse, and the spread of English has emerged not merely as a response to political and economic advancements, but also as the need for scientific progress and development, and the need in higher education in the region. As the role of English has been increasingly important in recent decades, official language policies have been based on both economic and political considerations, while various ideologies have also impacted the spread of English in the domain of education.